Digitalization of Working Worlds and Social Inclusion - Melchior, Alice (2023)
Digitalization is engendering profound societal transformation that is significantly restructuring our working lives. For society, and the world of work in particular, digitalization presents a major challenge, as the digital transformation of work does not simply relate to technological innovation; rather, it involves a complex sociotechnical process that is socially prepared, technically enabled, and discursively negotiated, and that ultimately must be individually mastered. As a result, the ongoing digitalization of “working worlds” is characterized by multiple dimensions and processes that evolve and proceed unevenly. These processes interact in complex ways, not uncommonly contradicting each other. Against this background, this thematic issue explores some of the implications and dynamics of the digital transformation of work concerning social inclusion.